2020
DOI: 10.1002/mp.13973
|View full text |Cite
|
Sign up to set email alerts
|

Detector response in the buildup region of small MV fields

Abstract: Purpose The model used to calculate dose distributions in a radiotherapy treatment plan relies on the data entered during beam commissioning. The quality of these data heavily depends on the detector choice made, especially in small fields and in the buildup region. Therefore, it is necessary to identify suitable detectors for measurements in the buildup region of small fields. To aid the understanding of a detector's limitations, several factors that influence the detector signal are to be analyzed, for examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Changes in the depth dose curves between the modifications 1 and 2 and the unmodified beam model as calculated in the treatment planning system (TPS) for a 10 × 10 cm 2 field. Additionally, response differences between two diodes, a PTW‐60012 and a photon field diode (PFD), relative to Gafchromic film are shown 35 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the depth dose curves between the modifications 1 and 2 and the unmodified beam model as calculated in the treatment planning system (TPS) for a 10 × 10 cm 2 field. Additionally, response differences between two diodes, a PTW‐60012 and a photon field diode (PFD), relative to Gafchromic film are shown 35 …”
Section: Methodsmentioning
confidence: 99%
“…Changes of the surface dose due to modification 3, relative to the unmodified beam model for a 10 × 10 cm 2 field. Additionally, the response difference between a PTW‐60008 detector and Gafchromic film is shown 35 …”
Section: Methodsmentioning
confidence: 99%
“…Besides the historical firm [28] it should be underlined that the number of vendors, such as [29][30][31] has increased in the past decade. The next important development is the growing diffusion of a commercial dosimeter, the PTW60019 microDiamond, which has become a reference dosimeter after many comparative studies with other types of dosimeters [32][33][34][35][36].…”
Section: Methodsmentioning
confidence: 99%
“…A changed detector response for the determination of depth-dose curves or relative distributions for photon beams with ionization chambers is usually not taken into account and the correction factor k NR is assumed to be unity. There are also several studies [36,37] that reported differences in the detector response in the build-up region Frontiers in Physics frontiersin.org depending on the choice of the EPOM. The study of Pena et al [36] assumed that if a measurement of a percentage depth-dose curve is performed without a shift of EPOM, further depth-dependent conversion factors should be used accounting for the variations in the depth-dependent detector response.…”
Section: Non-reference Correction Factor K Nr At Different Depths And...mentioning
confidence: 99%
“…The study of Pena et al [36] assumed that if a measurement of a percentage depth-dose curve is performed without a shift of EPOM, further depth-dependent conversion factors should be used accounting for the variations in the depth-dependent detector response. Wegener et al [37] could reduce the influence of different detector responses on relative measurements by using detector-individually derived effective points of measurement. This study showed that the non-reference correction factor k NR is depth-depending and varies likely by 3% for the Semiflex 3D and 2% for the SNC125c ™ due to different values of the specific fluence correction factors p i from constructive details and due to the depthdepending variations in the Spencer-Attix restricted stopping power ratios in an order of approximately 0.3% (Table 3).…”
Section: Non-reference Correction Factor K Nr At Different Depths And...mentioning
confidence: 99%